Antasenden Kecurangan Akuntansi Dengan Pengendalian Internal Sebagai Variabel Moderasi - Agintha, Nabilla Dwi (Jurnal Riset Akuntansi dan Bisnis, 2025)
This study uses an associative approach with a quantitative research type, and primary data sources obtained from distributing questionnaires. The sampling technique in this study uses the quota sampling technique, with 36 respondents. The analysis carried out in this study includes path analysis using the PLS application. Based on the results of the study, it was concluded that Compensation suitability has a positive and significant effect on Accounting Fraud in Hospitals throughout Medan City, meaning that when the company increases the implementation of good compensation suitability, it will increase the prevention of accounting fraud, Accounting information systems have a positive and significant effect on Accounting Fraud in Hospitals throughout Medan City, meaning that when the company increases the implementation of good accounting information systems, it will increase the prevention of accounting fraud, Internal control has a positive and significant effect in moderating the effect of compensation suitability on accounting fraud in Hospitals throughout Medan City